Let's solve for x.<span><span><span>3x</span>+<span>4y</span></span>=36</span>Step 1: Add -4y to both sides.<span><span><span><span>3x</span>+<span>4y</span></span>+<span>−<span>4y</span></span></span>=<span>36+<span>−<span>4y</span></span></span></span><span><span>3x</span>=<span><span>−<span>4y</span></span>+36</span></span>Step 2: Divide both sides by 3.<span><span><span>3x</span>3</span>=<span><span><span>−<span>4y</span></span>+36</span>3</span></span><span>x=<span><span><span><span>−4</span>3</span>y</span>+12</span></span>Answer:<span>x=<span><span><span><span>−4</span>3</span>y</span>+<span>12
i got dis
</span></span></span>
Alrighty
find where they intersect
9x²ln(x)=36ln(x)
divide both sides by 9
x²ln(x)=4ln(x)
so
so x=1 and and 2 (x can't be 0 or -2 because ln(0) and ln(-2) don't exist)
so intersect at x=1 and x=2
which is on top?
9(1.5)²ln(1.5)=20.25ln(1.5)
36ln(1.5)=36ln(1.5)
36ln(1.5) is on top
so
that will be
the area is
the area between the curves is 48ln(2)-29
Answer:
4 and -5 for the first one
-5 and -5 for the second
5 and -4 for the third
-4 and 5 for the fourth
Answer:
5x^2-13x+6
Step-by-step explanation:
(8x^2-6x+2)-(3x^2+7x-4)
8x^2-3x^2-6x-7x+2-(-4)
5x^2-13x+2+4
5x^2-13x+6